Topological and phenomenological classification of bursting oscillations - Bertram, Richard; Butte, Manish J.; Kiemel, Tim; Sherman, Arthur (Bulletin of mathematical biology, 1995)
We describe a classification scheme for bursting oscillations which encompasses many of those found in the literature on bursting in excitable media. This is an extension of the scheme of Rinzel (in Mathematical Topics in Population Biology, Springer, Berlin, 1987), put in the context of a sequence of horizontal cuts through a two-parameter bifurcation diagram. We use this to describe the phenomenological character of different types of bursting, addressing the issue of how well the bursting can be characterized given the limited amount of information often available in experimental settings.